(untitled) (Gaceta de Ciencias Veterinarias, 2018)
Semen characteristics of bulls may be affected by the environmental conditions of the places. Precipitation rate was determined for the area where the Centro de Inseminacion Artificial Carora (CIAC) is located, 12 km away from Carora city (Venezuela), and rainy as well as dry seasons were well established. Records of three consecutive years demonstrated that March, April, May, August, September, October and November showed the highest precipitations, whereas June, July, December, January and February were the driest months. Precipitation rate in the driest of all three years was 818 mm3, and that in the rainiest year was1289 mm3. Seminal traits of nine Carora bulls, 3 to 4 years old, from the CIAC were studied during two years (year 1 ranging from July 2005 to June 2006 and year 2 from July 2006 to June 2007), being significantly different in their precipitation levels; variables studied were: seminal volume, mass motility, percentage of mobile, progressive motility, vitality and total sperm abnormalities. No statistically significant differences were found for any of the seminal variables studied as related to rainy or dry months. However, when data was related to the year of study, statistically significant differences were established for 4 of the 6 seminal variables. These results suggest that precipitation rate in the rainy season did not directly improve seminal variables; however, semen quality was enhanced when precipitation rates exceed the zone annual average.